Konstruksi Citra Diri dalam Postingan Instagram Pada Mahasiswi Program Studi Ilmu Komunikasi Universitas Sebelas Maret Surakarta - Nirmala Sari, Dinda; Danang Purwanto (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
For some people, self-image is one of the needs that must be constructed to show their best branding to others, the purpose of this study is to see how female students build their self-image and explain the comparison of their self-image based on the posts uploaded with the reality of their lives. This study was written using a qualitative method with a phenomenological approach, samples were taken using a purposive sampling technique whose subjects were taken from female Communication Science students at Sebelas Maret University, the focus of this study was on individual views of posts on their personal accounts. The results of the study found that female students use Instagram to show their personal existence on social media, Instagram is used as a platform to build their self-image, especially those who are in the phase of finding their identity, the self-image they build tends to display a positive side in order to create a portfolio and positive assessments from other users. This study is associated with Erving Goffman's dramaturgy theory, where Instagram becomes the front stage displayed to the public and the reality of life is used as the back stage. A conclusion was drawn that female students always show a good self-image, they also avoid uploading things that might cause negative responses from their followers such as sadness, sarcasm, and various unethical posts with the aim of maintaining the self-image they have built